DAMPAK STATUS SOSIAL EKONOMI TERHADAP PARTISIPASI TENAGA KERJA WANITA DI SUMATERA BARAT - Trisanti Amelia; Idris (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of socioeconomic characteristics on the opportunities for working-age women to work in the informal sector in West Sumatra Province. The approach used is quantitative with a logistic regression method, based on secondary data from the 2020 National Socioeconomic Survey (SUSENAS) published by the Central Statistics Agency (BPS). The independent variables described include age, marital status, poverty status, education level, and area of residence. The estimation results show that every additional year of working-age women's age significantly increases the opportunity to work in the informal sector. In addition, marital status, coming from a poor household, having an education lower than high school, and living in a rural area also significantly increase the likelihood of women working in the informal sector. These findings emphasize the importance of policy interventions focused on improving access to education, economic empowerment, and equitable regional development to reduce gender inequality in the informal employment sector in West Sumatra. Keywords: informal sector, female labor, socioeconomic characteristics, logistic regression, West Sumatra.